Comparison of the Effect of Two Educational Methods on the Frequency of Hospitalization and Clinical Symptoms of Patients after Acute Myocardial Infarction - Parvaneh Asgari; Fatemeh Bahramnezhad; Soleyman Zand; Fatemeh Salehi; Fatemeh Rafiei (Journal of Holistic Nursing and Midwifery, 2018)
Introduction: Patient training can be effective in preventing and controlling disease complications. Providing patient and family trainings is particularly important for improving compliance with a treatment diet. Objective: The present study aimed at “determining the effect of two training methods (family-centered and patient-centered) on the frequency of hospitalization and clinical symptoms of patients after acute myocardial infarction”. Materials and Methods: This clinical trial was performed in the Heart Care Unit of one of the hospitals in Arak, Iran between October and March 2014. Here, 60 patients who had experienced their first heart attack were randomly selected and divided into two groups: patient training and family training. Thereafter, for the intervention group, each patient was trained with an active member of the family through a computer in three fields of food, medicine, motion in three sessions of 30-45 min, and in the control group the same training content was given only to the patient (without the family). At the time of discharge, the checklist of patients' clinical symptoms and the number of re-admittance was given to patients to be marked if they occurred. Three months after the intervention, the incidence of clinical symptoms and re-admission in the two groups were compared and evaluated. Finally, data was analyzed using Chi-square and independent t-test. Results: The two groups were significantly different in terms of demographic characteristics including age, gender, history of smoking and alcohol, occupation, familial history of cardiovascular disease, education, sport, and underlying diseases. The findings showed that the frequency of clinical symptoms including chest pain (P = 0.0001), Exertional dyspnea (P = 0.004), Orthopnea (P = 0.033), Paroxysmal Nocturnal Dyspnea (P = 0.03), Heart palpitations (P = 0.015) and the frequency of re-admittance (P = 0.015) were significantly lower in the family-based training group than patient-centered. Conclusion: According to the results of this study, implementation of training programs with the presence of families plays an important role in following the plan, subsequently improving the treatment outcomes and reducing the cost of treatment for patients. Therefore, it is recommended that family-centered training interventions be conducted.